Need for Treatment of Gonorrhea to be Effective against Chlamydia trachomatis - William R Bowie; Joanne Ast; Linda Sibau; Carol Shaw; Hugh D Jones; William A Black (Canadian Journal of Infectious Diseases)
Men and women with gonorrhea or contact to gonorrhea are frequently co-infected with Chlamydia trachomatis. To assess the importance of using treatment regimens active against both Neisseria gonorrhoeae and C trachomatis, tetracycline 500 mg orally four times daily for five days, with activity against both organisms, was compared with ceftriaxone, 250 mg once intramuscularly, with activity against only N gonorrhoeae. N gonorrhoeae microbiological failure occurred in six of 148 patients (4%) on tetracycline and zero of 85 on ceftriaxone. Microbiological failure for C trachomatis occurred in zero of 27 on tetracycline and 10 of 12 (83%) on ceftriaxone (P<0.001). In addition, 14 others on ceftriaxone had C trachomatis first isolated after treatment. When all types of microbiologialc and clinical failures are included, outcome was significantly better on tetracycline (P<0.001). Optimal treatment of patients with gonorrhea must include regimens with activity against both C trachomatis and N gonorrhoeae.